Acromioclavicular Joint Injuries in Professional Ice Hockey Players: Epidemiologic and MRI Findings and Association With Return to Play. Issue 11 (19th November 2020) - White, Lawrence M.; Ehmann, Jonathan; Bleakney, Robert R.; Griffin, Anthony M.; Theodoropoulos, John
Background: Acromioclavicular joint (ACJ) injuries are common in ice hockey players and are traditionally evaluated with conventional radiography, which has recognized limitations in the accurate characterization of the spectrum of soft tissue injuries and severity/grade of injury sustained. Purpose: To evaluate the epidemiologic, clinical, and magnetic resonance imaging (MRI) findings in professional ice hockey players who have sustained acute ACJ injuries. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review was performed of professional National Hockey League (NHL) players referred for MRI evaluation of acute ACJ injuries. All MRI scans were assessed for status of the ACJ, ligamentous stabilizers, and surrounding musculature. MRI-based overall grade of ACJ injury (modified Rockwood grade 1-6) was assigned to each case. Data regarding mechanism of injury, player handedness, clinical features, and return to play were evaluated. Results: Overall, 24 MRI examinations of acute ACJ injuries (23 patients; mean age, 24 years) were reviewed. We found that 50% of injuries were sustained during the first period of play, and in 75% of cases, injuries involved the same side as player shooting handedness. Analysis of MRI scans revealed 29% (7/24) grade 1 ACJ injuries, 46% (11/24) grade 2 injuries, 21% (5/24) grade 3 injuries, and 4% (1/24) grade 5 injuries. Trapezius muscle strains were seen in 79% and deltoid muscle strain in 50% of cases. Nonoperative management was used for 23 injuries; 1 patient (grade 5 injury) underwent acute reconstructive surgery. All players successfully returned to professional NHL competition. Excluding cases with additional injuries or surgery (n = 3) or convalescence extending into the offseason (n = 3), we found that the mean return to play was 21.4 days (7.2 games missed). No statistically significant difference was observed in return to play between nonoperatively treated grade 3 injuries (mean, 28.3 days) and grade 1 or 2 injuries (mean, 20.1 days). However, grade 3 injuries were associated with a greater number of NHL scheduled games missed (mean, 12.7) compared with lower grade injuries (mean, 6.1) ( P = .027). Conclusion: The spectrum of pathology and grading of acute ACJ injuries sustained in professional ice hockey can be accurately assessed with MRI; the majority of injuries observed in this study were low grade (grades 1 and 2). Although grade 3 injuries were associated with a greater number of games missed, similar return-to-play results were observed between nonoperatively treated grade 3 and grade 1 or 2 ACJ injuries.